2008
DOI: 10.2298/vsp0812906d
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polarized light therapy in pressure ulcer healing

Abstract: After a four-week polarized light therapy 20 patients with stage I-III ulcer had significant improvement in pressure ulcer healing, so it could be useful to apply polarized light in the treatment of pressure ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Even when polarized, UV-free, polychromatic light has been tested for various conditions, such as cutaneous and mucosal ulcerative lesions, 8 pressure ulcer healing, 44 acne vulgaris management, 45 diabetic foot complicated by atherosclerosis 46 and purulent- septic surgery, 47 more research is needed to understand its effect on NAD and other dermatological conditions. More clinical studies are needed to understand the therapeutic properties of polarized, UVfree, polychromatic light and to acknowledge its benefits, even though our findings suggest encouraging possibilities for the use of this therapy as a management strategy for recurrent moderate NAD.…”
Section: Discussionmentioning
confidence: 99%
“…Even when polarized, UV-free, polychromatic light has been tested for various conditions, such as cutaneous and mucosal ulcerative lesions, 8 pressure ulcer healing, 44 acne vulgaris management, 45 diabetic foot complicated by atherosclerosis 46 and purulent- septic surgery, 47 more research is needed to understand its effect on NAD and other dermatological conditions. More clinical studies are needed to understand the therapeutic properties of polarized, UVfree, polychromatic light and to acknowledge its benefits, even though our findings suggest encouraging possibilities for the use of this therapy as a management strategy for recurrent moderate NAD.…”
Section: Discussionmentioning
confidence: 99%
“…This launches cellular chain responses and triggers what so-called secondary responses, which are not only confined to the treated skin area nevertheless; it can affect the entire body. The mechanisms of action are not quite clear, despite being revealed in terms of photobiomodulation [11,12]. The literatures review revealed biom-odulation as the manner of altering the routine biochemical response of a cell or tissue within the usual range of its role to excite the cell's intrinsic metabolic potential to react to a stimulus [13,14].…”
mentioning
confidence: 99%
“…PL is widely used in the treatment of various types of wounds, including burn wounds to the skin and pressure ulcer. 32,33 Considering these 2 mentioned modalities (PL and LLLT) in the treatment of pain syndromes, the goal of this study was to examine the effectiveness of polarized lowlevel laser therapy (PLLLT) in the reduction of pain of MTrPs in the trapezius. We also compared its effectiveness in pain control with LLLT.…”
Section: Introductionmentioning
confidence: 99%